2011
DOI: 10.1002/jmri.22488
|View full text |Cite
|
Sign up to set email alerts
|

Automated ischemic lesion detection in a neonatal model of hypoxic ischemic injury

Abstract: Purpose: To develop and compare an automated detection system for ischemic lesions in a neonatal model of bilateral carotid artery occlusion with hypoxia (BCAO-H) from T2 weighted MRI (T2WI) to the currently used ''gold standard'' of manual segmentation.Materials and Methods: Forty-three P10 BCAO-H rat pups and 8 controls underwent T2WI at 1 day and 28 days. A computational imaging method, Hierarchical Region Splitting (HRS), was developed to automatically and rapidly detect and quantify 3D lesion and normal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 62 publications
1
54
0
Order By: Relevance
“…We have previously reported that HRS can rapidly and precisely define T2-map volumes of ischemic injury in a rat-pup model of global ischemia. 15 Refinement of our computational approach now provides strong evidence that: (1) HRS can detect and quantify the core-penumbra in focal and global models of ischemia using ADC/T2-map data that match IHC measures; (2) HRS from a single MR modality (T2WI) is as good as DPM in detecting core-penumbra; and (3) HRS works equally well in term newborns with AIS. We have purposefully varied injury severity (from mild to severe) to show successful applicability of HRS to a broad range of data.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…We have previously reported that HRS can rapidly and precisely define T2-map volumes of ischemic injury in a rat-pup model of global ischemia. 15 Refinement of our computational approach now provides strong evidence that: (1) HRS can detect and quantify the core-penumbra in focal and global models of ischemia using ADC/T2-map data that match IHC measures; (2) HRS from a single MR modality (T2WI) is as good as DPM in detecting core-penumbra; and (3) HRS works equally well in term newborns with AIS. We have purposefully varied injury severity (from mild to severe) to show successful applicability of HRS to a broad range of data.…”
Section: Discussionmentioning
confidence: 91%
“…Detection of core-penumbra builds on our published HRS algorithm 15 by further dichotomizing the extracted injury regions (i.e., lesion). The HRS extraction of the lesion encompasses: (1) skull stripping; (2) removing background noise; (3) rescaling MR values to reduce computational complexity; (4) modeling the histogram of the rescaled MR values as a bimodal distribution with two distinct and distant peaks; (5) splitting the MR image into two subimages using the valley between these two peaks in the histogram; (6) recursively resplitting the bimodal distributions to generate the HRS tree; (7) stopping the recursive splitting based on a set of uniformity criteria; (8) converting the rescaled values back to actual MR values; and (9) extracting the lesion volume based on 'a priori' approximate mean MR values (using a threshold meanTh; Table 1).…”
Section: Hierarchical Region Splitting Computational Assessment Of Comentioning
confidence: 99%
See 1 more Smart Citation
“…These Gaussian distributions can be closely spaced, i.e., the mean MR signal intensity of different tissues are close, so that on occasion, one needs to consider fuzzy connectedness where class membership values are like weights in GMM but with "fuzzyness," in which the probabilities of a voxel being in tissue A and tissue B are assigned [ 31 ] . However, histogram fi tting to a normalized histogram, as adapted by Fan and colleagues, cannot be used when large lesions affect the shape of the histogram [ 32 ] .…”
Section: Gaussian Mixed Modelsmentioning
confidence: 99%
“…42.1 ). ) and overlap (sensitivity: 0.82, specifi city: 0.86, similarity: 1.47) to manually extracted results [ 32 ] . Although the methods and results of HRS were obtained from MR images, HRS is a generic method for any medical image (e.g., MRI, PET, CT) where contrast in the medical image is used to detect abnormalities.…”
Section: Hierarchical Region Splittingmentioning
confidence: 99%